The number of CD163 positive macrophages is associatedwith more advanced skin melanomas, microvessels density and patient prognosis - Foks, Maciej; Wągrowska-Danilewicz, Małgorzata; Danilewicz, Marian; Bonczysta, Marta; Olborski, Bogusław; Stasikowska-Kanicka, Olga (Polish Journal of Pathology, 2019)
The study was aimed to evaluate the number of TAMs and to investigate whether they have association with microvessels density and patients’ survival times. 46 cases of melanomas, divided into four groups according to the Breslow scale, were tested immunohistochemically with antibodies anti-CD68, CD163, iNOS to vizualized macrophages and anti-CD34 antibody to stain microvessels. The number of macrophages and the microvessels density were counted by hotspot analysis using an image analysis system. The study revealed increased numbers of CD68 and CD163 positive macrophages in successive stages of Breslow scale, but statistically significant differences were observed only between I and IV group for CD68 positive macrophages, and between I and III, IV group for CD163 positive macrophages. The mean number of the microvessels was significantly increased in group II, III, IV compared to group I. The correlative study showed significant positive correlations between the mean number of CD68 and CD163 positive macrophages and microvessels density. Moreover, the number of CD163 positive macrophages was associated inversely with patient’s survival time. The results of our study may indicate that higher infiltration of macrophages, especially CD163 positive cells, is associated with more advanced melanomas, microvessels density and worse patient’s prognosis.